Shallow estuarine reef as nursery habitat for Australasian snapper ( Chrysophrys auratus ) - Jessica L. Campbell; Mark A. Morrison; Richard B. Taylor (New Zealand Journal of Marine and Freshwater Research, 2025)
Estuaries are important recruitment sites for many fish species, with structurally‐complex habitats such as subtidal seagrass beds on soft sediments particularly valuable due to their provision of food and shelter. Soft sediments dominate most estuaries, but where hard‐bottom reefs are present they have the potential to act as nursery habitats for juvenile fish. We document recruitment of juvenile Australasian snapper ( Chrysophrys auratus ) to a shallow linear sandstone reef in Whangateau Harbour, a small estuary in north‐eastern New Zealand. Up to several hundred 0 + juveniles (∼20–70 mm fork length) were present on the reef during early summer to mid‐late autumn each year from 2018 to 2021. Numbers were consistently highest at the seaward end of the reef, facing into incoming tidal currents, and lowest in the deeper central part of the reef, where larger, potentially cannibalistic, snapper were common. Juveniles disappeared from the reef fairly abruptly at the end of each season, with departure in at least two of the years appearing to follow a sudden decrease in water temperature rather than being associated with body size or absolute temperature. Although relatively small in area, estuarine reefs may be increasingly important nursery habitats in the future given the widespread loss of subtidal seagrass beds.